Dicrostonyx nelsoni Merriam 1900 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Dicrostonyx nelsoni Merriam 1900 Dicrostonyx nelsoni Merriam 1900, Proc. Wash. Acad. Sci., 2: 25. Type Locality: USA, Alaska, Norton Sound, St. Michael. Vernacular Names: Nelson's Collared Lemming. Synonyms: Dicrostonyx exsul G. M. Allen 1919; Dicrostonyx peninsulae Handley 1953. Distribution: W Alaska and Alaska Peninsula, USA. Conservation: IUCN – Data Deficient as D. exsul , Lower Risk (lc) as D. nelsoni . Discussion: Rausch and Rausch (1972) noted successful mating among F1 progeny of D. nelsoni and collared lemmings on St. Lawrence Isl ( exsul ), while Jarrell and Fredga (1993) reported meiotic incompatibility and reduced fertility between stocks of D. nelsoni and rubricatus (= D. groenlandicus ). In view of the complex appearance of Beringia refugia in space and time and the possibility of isolation from northern or southern stocks (e.g., see MacDonald and Cook, 1996), the homogeneity of populations in western Alaska ( D. nelsoni ) and those of D. groenlandicus should be empirically demonstrated, including samples from Beringean landbridge islands ( exsul and D. vinogradovi ), the Alaska Peninsula ( peninsulae ), and Aleutian chain ( D. unalascensis ). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia - Family Cricetidae, pp. 955-1189 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 2, Baltimore :The Johns Hopkins University Press on page 972, DOI: 10.5281/zenodo.7316535